Investigating death: the emotional and cultural challenges for police. (17th August 2016) - Carpenter, Belinda; Tait, Gordon; Quadrelli, Carol; Thompson, Ian
Abstract : The over-representation of vulnerable populations within the criminal justice system, and the role of police in perpetuating this, has long been a topic of discussion in criminology. What is less discussed is the way in which non-criminal investigations by police, in areas like a death investigation, may similarly disadvantage and discriminate against vulnerable populations. In Australia, as elsewhere, it is police who are responsible for investigating both suspicious and violent deaths like homicide as well as non-suspicious, violent deaths like accidents and suicides. Police are also the agents tasked with investigating deaths, which are neither violent nor suspicious but occur outside hospitals and other care facilities. This paper, part of a larger funded Australian research project focusing on the ways in which cultural and religious differences are dealt with during the death investigation process, reports on how police describe – or are described by others – during their role in a non-suspicious death investigation, and the challenges that such investigations raise for police and policing. The employment of police liaison officers is discussed as one response to the difficulty of policing cultural and religious difference with variable results.